On-Chip Antenna for Electronic Photonic Integrated D-Band Wireless Applications - Tas, Deniz; Breun, Sascha; Hagelauer, Amelie; Dietz, Marco; Weigel, Robert (Asia-Pacific Microwave Conference Proceedings, APMC, 2024)
This paper presents the implementation of an on-chip double folded dipole antenna using backside etching technique derived from a silicon photonic SiGe BiCMOS approach. Silicon photonics have found extensive utilisation in communication data center applications however there is not much research for wireless communication, radar and sensing applications. In this paper, a folded dipole antenna, by the etching the electronic photonic technology, targeting the frequency bandwidth the mid of D-Band has been designed and measured on the wafer prober. To the best of the authors knowledge, it is the first on-chip D-Band antenna for EPIC process.
CRIS-Team Scopus Importer:2025-04-01
Keywords: antenna; electronic photonic integrated circuit; LBE